2017
DOI: 10.3389/fimmu.2017.00434
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Non-Human Leukocyte Antigen-Specific Antibodies in Kidney and Heart Transplantation

Abstract: The presence of donor human leukocyte antigen (HLA)-specific antibodies has been shown to be associated with graft loss and decreased patient survival, but it is not uncommon that donor-specific HLA antibodies are absent in patients with biopsy-proven antibody-mediated rejection. In this review, we focus on the latest findings on antibodies against non-HLA antigens in kidney and heart transplantation. These non-HLA antigens include myosin, vimentin, Kα1 tubulin, collagen, and angiotensin II type 1 receptor. It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
23
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 66 publications
1
23
0
1
Order By: Relevance
“…14 AVA is associated with increased premature coronary artery disease, but not early rejection or graft survival in cardiac transplant recipients. 4,10,16,17 Global production of vimentin throughout the kidney and its exposure to the immune system increase in response to apoptosis and endothelial injury, such as occurs during peritransplantation IRI or after rejection. [5][6][7][8] AVA is associated with focal proximal tubular vimentin expression and subclinical rejection by 21 days after kidney transplantation in rhesus monkeys.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 AVA is associated with increased premature coronary artery disease, but not early rejection or graft survival in cardiac transplant recipients. 4,10,16,17 Global production of vimentin throughout the kidney and its exposure to the immune system increase in response to apoptosis and endothelial injury, such as occurs during peritransplantation IRI or after rejection. [5][6][7][8] AVA is associated with focal proximal tubular vimentin expression and subclinical rejection by 21 days after kidney transplantation in rhesus monkeys.…”
Section: Discussionmentioning
confidence: 99%
“…2 However, non-HLA donor-specific memory responses can also play an important pathogenic role in acute antibody-mediated rejection (AMR), 3 and several non-HLA antibodies have been implicated. 4 We report a case of postoperative day 2 AMR in an unsensitized, cross-match-negative, haplotypematched, living donor kidney transplant recipient with preformed anti-vimentin antibody (AVA). Ischemia-reperfusion injury (IRI) can increase the surface expression of vimentin in apoptotic renal tubular epithelial and endothelial cells, providing a plausible mechanism for exposure of donorspecific antigenic targets to cause anti-vimentin AMR.…”
Section: Introductionmentioning
confidence: 99%
“…HLA is essential for assessing the likelihood of transplant rejection, a higher degree of HLA match indicates a reduced probability of transplant rejection ( 52 ). In the present study, no difference between clinical response and OS was observed in patients with diversified degrees of HLA match.…”
Section: Discussionmentioning
confidence: 99%
“…Non‐HLA antibodies such as antibodies against AT1R, vimentin, myosin, and other endothelial cell (EC) antigens are prevalent among ventricular assist device (VAD) patients . Anti‐AT1R antibodies are known to initiate coagulation and inflammatory responses independent of the complement cascade . There are conflicting reports about whether anti‐AT1R and EC antibodies play a role in cardiac allograft survival …”
Section: Introductionmentioning
confidence: 99%